The Taghas's; Foundations and Sources Comparative study (Emamiyeh Jurisprudence, Iran, UK and USA law) - Rasoul Ahmadi Far (پژوهش‌نامه حقوق اسلامی, 2017)
In the Iranian legal source of law the judiciary is the sole official reference for adjudication, and there is no place in this regard for Taghas. In the other source of law in Iran, including valid jurisprudential sources, custom and doctrine, the Taghas declared and is the non-judicial ways for adjudication. Some of the law system like the UK and USA (self-help) declared as a one of the extrajudicial remedy. So, the first issue in the current study is: (The study for possibility of permit of Taghas on the base of costume, valid jurisprudential and Doctrine). Second issue is opting out the correct equivalent for Taghas in legal systems studied. In the based on this study though although the legal source of Iranian law is the prohibition of invalidity of Taghs but due to its function and justifiability in the jurisprudence and doctrine appropriate action should be taken by policy-makers to legislate to allow Taghs, and current equivalent for Taghas in the legal system studied is (self-help).